Comparison of DNA Concentration and Purity of Animal Blood Extracted using Different DNA Extraction Kits - Mohamed Sabri Esa; Nur Huda Faujan; Haitham Abdullah Rajab; Maryam Mohamed Rehan; Norlelawati Arifin; Alina Abdul Rahim (Universiti Sains Islam Malaysia, 2024)
The efficiency of DNA extraction from whole blood using appropriate method is very important for molecular analysis. Therefore, the aim of this study was to compare the purity and concentration of DNA extraction method from bovine (Bos taurus), chicken (Gallus gallus), and porcine (Sus scrofa) blood. The DNA of blood samples was extracted using three types of kit, namely InnuPREP Blood DNA Mini Kit, Wizard Genomic DNA Purification Kit, and QIAamp DNA Blood Mini Kit. The results showed that blood DNA extracted using QIAamp DNA Blood Mini Kit was found to be the most effective and consistently produced high concentrated and pure DNA for three animal samples. The purity of DNA ranged from 1.73 ' 0.05 ' to 1.94 ' 0.21 ' and the range of blood DNA concentration extracted using the QIAamp DNA were between 13.73 - 2.11 and 25.01 - 2.08 ng/?l. However, the blood DNA of porcine was not successfully extracted using InnuPREP Blood DNA Mini Kit and Wizard Genomic DNA Purification Kit. These results were very crucial for the subsequent use of amplification using polymerase chain reaction (PCR) and to facilitate accurate detection in further analysis.